Local Communities Implications’ in Managing Woody Species and Carbon Accumulation in Sahelian parts of Maradi Region, Niger Republic - Abdourahamane, Mamane; A. Yusuf, Maharazu; Massaoudou, Moussa (International Journal of Scientific Research and Management (IJSRM), 2024)
In Sahel, climate change will intensify especially in West Africa in the future and seasons are observed to have a decrease in rainfall projected. This situation will affect future woody vegetation cover because Sahelian zone was characterized by significant vegetation response to rainfall. Notwithstanding climate change impacts on woody vegetation cover, some human practices can play positive role in Sahelian vegetation change. This study aimed to analyze local community implications’ in managing woody species and carbon accumulation in Sahelian parts of Maradi Region, Niger Republic. Both quantitative and qualitative data were used in this study. Results showed that ecosystem services (provisioning, regulating and supporting) provided by woody trees species in the study area represent the main reasons for maintenance and protection of trees in farmlands. This clearly highlighted the roles of local communities in maintenance and protection of woody trees and consequently carbon accumulation by these woody species. This can allow farmers to be eligible to receive payments for the ‘’Carbon’’ that those practices contribute to sequester under a ‘’Carbon’’ trading arrangement in the Clean Development Mechanism (CDM) of the Kyoto Protocol of United Nations Framework Convention on Climate Change.